Using High-Power UV-LED to Accelerate a Decatungstate-Anion-Catalyzed Reaction: A Model Study for the Quick Oxidation of Benzyl Alcohol to Benzoic Acid Using Molecular Oxygen - Mamoru Hyodo (MDPI AG, 2021)
High-power UV-LED irradiation (365 nm) effectively accelerated the decatungstate-anion-catalyzed oxidation of benzyl alcohol 1 to benzoic acid 3 via benzaldehyde 2. As the power of the UV-LED light increased, both the selectivity and yield of benzoic acid also increased. The reaction was finished within 1 h to give 3 in a 93% yield using 2 mol% of decatungstate anion catalyst. The combination of a flow photoreactor and high-power irradiation accelerated the oxidation reaction to an interval of only a few minutes.